Response to unexpected social inclusion: A study using the cyberball paradigm - Groth, Rosa-Marie; Rief, Winfried (Frontiers in Psychiatry, 2022)
Background Dysfunctional expectations are considered core characteristics of Major Depressive Disorder (MDD) and should be focused in psychotherapy. Dysfunctional expectations are especially pronounced in the interpersonal area (social expectations). In the present study, we examine the effect of unexpected social inclusion (expectation violation) on the change of generalized and specific depression-typical social expectations. Method We conducted an online study to investigate the impact of social inclusion after a period of social exclusion (unexpected social inclusion) on social expectation change (sample size 144) in a non-clinical sample. Depressive symptoms were assessed via self-reporting. Participants took part in two rounds of the online ball-game Cyberball. In the first round, all participants were socially excluded by their two co-players (acquisition of negative social expectations). In the second round, participants were either once more excluded (expectation confirmation) or included equally (expectation violation) by the same co-players. Specific and generalized social expectations were assessed after each round. Results Specific and generalized social expectations increased following expectation violation. Even though depressive symptoms were related to lower levels of social expectations, we found that depressive symptoms did not moderate expectation change after positive expectation violations. Conclusions In the present experimental setup including the use of the online ball-game Cyberball, the establishment and change of social expectations can be experimentally manipulated. Under the given circumstances and in a non-clinical sample, negative expectations can be updated after unexpected positive experiences regardless of the number of depressive symptoms. The results are discussed in the context of current models of Major Depressive Disorder (MDD), expectation change, and cognitive behavioral therapy.